Prototype of movement monitoring Objects using Arduino Nano and SMS Notifications - Lupitha, Mariska; Haryono, Haryono (Politeknik Ganesha Medan, 2022)
Currently, the development of information technology is very rapid, coupled with the development of the internet of things which is also very fast. This encourages many researchers to use information technology devices and internet of things devices to solve problems in the field. The Internet of things is a device that can communicate between one device and another. Currently, there are many internets of things devices that have been used in everything, including Smart Home, Smart Office, Smart Campus, and others. There is a problem, where currently there is a lot of theft of goods or the transfer of goods that are not known by the owner. This problem encourages researchers to conduct research, by making prototypes to be able to find out about objects that have moved. So that the owner of the goods will know, that the goods have moved without notifying the owner. This research is to detect motion sensors using MPU6050. Where the sensor has two functions, namely accelerometer, and gyroscope. Both sensors are able to find the coordinates of the x-axis, y-axis, and z-axis. The most widely used and affordable microcontroller is the Arduino Nano or Arduino Uno. The purpose of this study is to detect motion with the MPU6050 sensor, then the detection results of the x-axis, y-axis, and z-axis are sent via SMS media with the SIM900A device. The use of a prototype has many functions, it can be used to detect falling objects, detect falling motorcycles, and others. This device is equipped with a SIM900A module which functions to transmit coordinate data via Short Message Service (SMS).